(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2021)
The paper shows the rules of activity-based costing in public administration during crisis management. The usage of this account is important, especially for spending li-mited public funds, when an organization can precisely estimate the cost of its individu-al crises. Apart from that in the paper one can find a new vision of crisis management based on processes and costs, which involves dealing with threats before and after they have occurred.